PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA FAVE HOTEL KUTA KARTIKA PLAZA - I Putu Andrayana; I Made Hedy Wartana (Journal Research of Management, 2020)
Employee performance is a very important thing in the organization's business to achieve company goals so that various activities must be carried out by the company to achieve its objectives and continue to improve the performance of its employees, one of which is to set appropriate performance standards and performance appraisal. This study aims to determine whether or not there is a simultaneous or partial influence between leadership and communication on employee performance at Fave Hotel Kuta Kartika Plaza. This research was also conducted to find out which variables had a more dominant influence on employee performance at Fave Hotel Kuta Kartika Plaza. The respondents of this study were 65 employees of Fave Kuta Hotel Karika Plaza. The data analysis technique used is multiple linear regression analysis techniques. T test is used to determine the effect of independent variables on the dependent variable partially and the F test is used to determine the significant effect of independent variables on the dependent variable together (simultaneous). Based on the results of the analysis, it is known that leadership and communication together have a significant effect on the performance of employees of Fave Hotel Kuta Kartika Plaza. This can be seen from the results of the t test, the leadership and communication variables partially have a positive effect on employee performance, where leadership has a value of t arithmetic (8,035)> t table (1,670). Furthermore, the F test is where F count 38.081> from the value of F table 3.145 while the most dominant variable influencing employee performance is the leadership variable of 0.686> of the communication variable 0.348. Based on the results of the study, it can be suggested that company leaders are expected to be more open in giving directions to subordinates, good and effective communication so that they continue to be intertwined between superiors and subordinates or fellow employees in the company.